2012
DOI: 10.1007/s11033-012-2306-4
|View full text |Cite
|
Sign up to set email alerts
|

FATP1 silence inhibits the differentiation and induces the apoptosis in chicken preadipocytes

Abstract: FATP1 plays an important role in the trafficking of free fatty acids in adipocytes, however, its precise function and relationship with other fatty acid transporters all remain poorly understood. In this study, FATP1 gene silencing was induced by transfecting siRNA of target sequence into chicken preadipocytes, then the expression of FABP was found down-regulated while the expression of FAT was raised. In addition, differential inhibition of the cells was observed and the expressions of PPARγ and C/EBPα were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…Since previous studies have reported an antiapoptotic role for FATP1 [25], we speculated that hFATP1 might inhibit the wave of PR apoptosis that occurs during NR development. To assess our hypothesis, we used the TUNEL assay to analyze the number of apoptotic cells in the NR of transgenic and WT mice on postnatal (P) days 6, 9, and 12 (Fig 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous studies have reported an antiapoptotic role for FATP1 [25], we speculated that hFATP1 might inhibit the wave of PR apoptosis that occurs during NR development. To assess our hypothesis, we used the TUNEL assay to analyze the number of apoptotic cells in the NR of transgenic and WT mice on postnatal (P) days 6, 9, and 12 (Fig 7).…”
Section: Resultsmentioning
confidence: 99%
“…We showed here that mice Bcl-2 and Bax mRNAs are upregulated and downregulated, respectively, by hFATP1 overexpression. Likewise, Qi et al [25] demonstrated that FATP1 silencing significantly increased the expression and activities of the proapoptotic factors caspase 3 and Bax. Interestingly, in Drosophila , fatp deficiency causes loss of PRs via a caspase-dependent death pathway, suggesting an important conserved function for FATP in PR survival [18].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have shown that PPAR γ and C/EBP α (Yu et al 2014), as well as FATP1 (Qi et al 2013) and Klf7 (Zhang et al 2013) regulate the differentiation of preadipocytes in the chicken. However, to our knowledge, investigations into the roles of lncRNAs in preadipocyte differentiation in the chicken have not yet been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes have been identified as regulators of adipogenesis and preadipocyte differentiation in chickens, including KLF2 (Zhang et al 2014a), KLF3 (Zhang et al 2014b), and FATP1 (Qi et al 2013). Several recent studies have investigated the regulatory mechanisms of chicken adipogenesis using genome-wide analysis of mRNA (Ji et al 2012; Regassa and Kim 2015) and microRNA (Wang et al 2015).…”
mentioning
confidence: 99%
“…antibodies, available and few transgenic animals. Gene silencing by siRNA are now routinely used in studies on cattle (Ma and Corl, 2012), sheep (Smith et al, 2012), chickens (Qi et al, 2013), pigs (Shi et al, 2013) and salmon (Kumari et al, 2013) using cell lines and some primary cells. However, there are difficulties introducing exogenous nucleotides, including siRNA, into certain primary cells, especially primary macrophages (reviewed by Zhang et al, 2009) and studies using siRNA to investigate macrophage genes lag behind those for other cell types.…”
Section: Introductionmentioning
confidence: 99%